Application of the Problem Based Learning Model to Improve Learning Outcomes in the Religious Moral Development Methodology Subject for Early Childhood Pg Paud Study Program - I Putu Suwika; Nurhayati; Andi Agusniatih (East Asian Journal of Multidisciplinary Research, 2023)
The aim of the research is to describe the implementation of the problem-based learning model to improve student learning outcomes in the subject of religious development methodology, children's morals. The method used is Classroom Action Research (CAR) and 2 cycles, there are 4 steps: Planning, action implementation, observation and reflection, and the subjects of this study were PGPAUD Study Program students. Furthermore, the technique used in collecting data uses observation sheets, tests and documentation. The technique in analyzing the data uses the average value formula, presentation of learning completeness and data observation. Learning using problem-based learning can improve the learning outcomes of PG PAUD study program students in the Development course of moral and religious values ​​for early childhood.The results showed that before the implementation of the based learning model, the minimum mastery standard criteria (KKM) were still low. After implementing the problem based learning model, there was an increase in learning outcomes, indicating an increase in learning completeness in each cycle.